Professional Java Server Programming (Wrox Press, 2000)
The release of the 1.3 version of the Java 2 Platform, Enterprise Edition (J2EE) represents the evolution of Sun Microsystems' server-side development platform into a more mature and sophisticated specification. Servlets 2.3 gain events and filtering; JavaServer Pages (JSP) 1.2 gain a new XML syntax and enhancements to the custom tag mechanisms; and Enterprise JavaBeans (EJB) 2.0 has some significant changes to its container-managed persistence model, as well as support for asynchronous processing with the new message-driven beans. This book demonstrates how to design and construct secure and scalable n-tier J2EE applications, using JSP and servlets for the web tier and EJBs for the business logic. It also covers J2EE Connector Architecture that allows you to easily integrate your J2EE applications to enterprise information systems.